High‐Operating‐Temperature Direct Ink Writing of Mesoscale Eutectic Architectures. Issue 7 (15th December 2016) - Boley, J. William; Chaudhary, Kundan; Ober, Thomas J.; Khorasaninejad, Mohammadreza; Chen, Wei Ting; Hanson, Erik; Kulkarni, Ashish; Oh, Jaewon; Kim, Jinwoo; Aagesen, Larry K.; Zhu, Alexander Y.; Capasso, Federico; et al.
Abstract : High‐operating‐temperature direct ink writing (HOT‐DIW) of mesoscale architectures that are composed of eutectic silver chloride–potassium chloride. The molten ink undergoes directional solidification upon printing on a cold substrate. The lamellar spacing of the printed features can be varied between approximately 100 nm and 2 µm, enabling the manipulation of light in the visible and infrared range.